MISSION OVER ADAPTABILITY: HOW CULTURE AND ENVIRONMENT JOINTLY DRIVE PERFORMANCE IN TRADITIONAL SMES - Natsir, Uhud Darmawan (Nusantara Economics and Entrepreneurships Journals, 2025)
Purpose: This study investigates the direct and interactive effects of organizational culture and the physical-psychosocial work environment on employee performance within small and medium-sized enterprises (SMEs), specifically in the traditional brick-making industry in Takalar Regency, Indonesia. Design/methodology/approach: A quantitative approach was employed using a cross-sectional survey. Data were collected from 150 employees across 20 brick-making units through structured questionnaires measuring organizational culture (adaptability, consistency, mission, involvement), work environment (safety, equipment, peer support), and performance (task, contextual). Data analysis used Structural Equation Modeling (SEM-PLS) to test the hypotheses. Findings: The results indicate that both organizational culture and work environment have significant positive effects on employee performance. Furthermore, a positive organizational culture was found to strengthen the positive impact of a conducive work environment on performance. The "mission" dimension of culture and "safety" aspect of the environment emerged as the most influential factors. Research limitations/implications: The study's cross-sectional design limits causal inferences. Future research should incorporate longitudinal data and expand to other labor-intensive traditional industries. Practical implications: Owners/managers of traditional SMEs should focus on building a clear, shared mission and values while critically investing in safer physical infrastructure and fostering peer support to enhance productivity sustainably. Originality/value: This study fills a critical gap by examining the under-researched context of informal, traditional manufacturing SMEs. It provides empirical evidence on how socio-cultural factors and physical conditions jointly influence performance in a resource-constrained setting, offering a nuanced perspective beyond mainstream organizational studies.